Food taboos, health beliefs, and gender: understanding household food choice and nutrition in rural Tajikistan - Katharine McNamara; Elizabeth Wood (BMC, 2019)
Abstract Household nutrition is influenced by interactions between food security and local knowledge negotiated along multiple axes of power. Such processes are situated within political and economic systems from which structural inequalities are reproduced at local, national, and global scales. Health beliefs and food taboos are two manifestations that emerge within these processes that may contribute beneficial, benign, or detrimental health outcomes. This study explores the social dimensions of food taboos and health beliefs in rural Khatlon province, Tajikistan and their potential impact on household-level nutrition. Our analysis considers the current and historical and political context of Tajikistan, with particular attention directed towards evolving gender roles in the wake of mass out-migration of men from 1990 to the present. Considering the patrilieneal, patrilocal social system typical to Khatlon, focus group discussions were conducted with the primary decision-making groups of the household: in-married women, mothers-in-law, and men. During focus groups, participants discussed age- and gender-differentiated taboos that call for avoidance of several foods central to the Tajik diet during sensitive periods in the life cycle when micronutrient and energy requirements peak: infancy and early childhood (under 2 years of age), pregnancy, and lactation. Participants described dynamic and complex processes of knowledge sharing and food practices that challenge essentialist depictions of local knowledges. Our findings are useful for exploring entaglements of gender and health that play out across multiple spatial and temporal scales. While this study is situated in the context of nutrition and agriculture extension, we hope researchers and practitioners of diverse epistemologies will draw connections to diverse areas of inquiry and applications.